Pengaruh Good Corporate Governance terhadap Manajemen Laba pada Perusahaan Sektor Kesehatan - Zava Nuruzzuhrotil Ula; Nurul Qomariyah; Shafiyya Zahra (Faculty of Economics and Business, Universitas Mahasaraswati Denpasar, 2024)
Good corporate governance (GCG) is an important aspect in corporate management, especially in the healthcare sector. This is because good Good corporate governance (GCG) practices can affect the transparency and accountability of financial reports, as well as reduce the tendency of earnings management. The risk of earnings management is often used in the face of pressure to maintain stable and attractive financial performance for stakeholders. This study aims to analyze the effect of good corporate governance on earnings management in healthcare sector companies. This study uses a quantitative approach with an explanatory research to test the effect of Good corporate governance (GCG) on earnings management in health sector companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The results obtained from this study are independent commissioners, managerial ownership, institutional ownership do not have a significant effect on earnings management. While the audit committee has a significant effect on earnings management. Independent commissioners, managerial ownership, institutional ownership and audit committees simultaneously have a significant effect on earnings management.